Community-Based Prescribing for Impetigo in Remote Australia: An Opportunity for Antimicrobial Stewardship - Oliver, Stefanie Jane; Cush, James; Ward, Jeanette E. (Frontiers in Public Health, 2017)
ABSTRACT Background To support antibiotic prescribing for both hospital and community-based health professionals working in remote northwestern Australia, a multidisciplinary Anti-Microbial Stewardship (AMS) Committee was established in 2013. This Committee is usually focused on hospital-based prescribing. A troubling increase in sulfamethoxazole/ trimethoprim (SXT) resistance in Staphylococcus aureus antibiograms from 9% to 18% over one year prompted a shift in gaze to community prescribing. What we did Finding a paucity of relevant research, we first investigated contextual factors influencing local prescribing. We also designed a systematic survey of experts with experience relevant to our setting using a structured response survey (12 questions) to better understand specific AMS risks. Using these findings, recommendations were formulated for the AMS Committee. What we learned Prescribing recommendations in a regional Skin Infections Protocol had previously been altered in December 2014. From 15 experts, we received nine comprehensive responses (60%) about AMS risks in community prescribing. If feasible, prescribing audits also would have been valuable. Ten recommendations regarding specific antibiotic recommendations were submitted to the AMS Committee. Strengthening AMS in remote settings As AMS committees in Australia usually focus on hospital-based prescribing, novel methods such as external expert opinion could inform deliberations about community-based prescribing. Our approach meant that this AMS Committee was able to intervene in the 2017 organisational review of the regional Skin Infections Protocol used by prescribers likely unaware of AMS risks. This experience demonstrates the value of incorporating AMS principles in community-based prescribing in context of a remote setting.